Neutrosophic Semiopen Hypersoft Sets with an Application to MAGDM under the COVID-19 Scenario. (30th April 2021) - Ajay, D.; Charisma, J. Joseline; Boonsatit, N.; Hammachukiattikul, P.; Rajchakit, G.
Abstract : Hypersoft set is a generalization of soft sets, which takes into account a multiargument function. The main objective of this work is to introduce fuzzy semiopen and closed hypersoft sets and study some of their characterizations and also to present neutrosophic semiopen and closed hypersoft sets, an extension of fuzzy hypersoft sets, along with few basic properties. We propose two algorithms based on neutrosophic hypersoft open sets and topology to obtain optimal decisions in MAGDM. The efficiency of the algorithms proposed is demonstrated by applying them to the current COVID-19 scenario.